Therapy and prophylaxis of sepsis - Targowski, Tomasz; Płusa, Tadeusz (Przewodnik Lekarza/Guide for GPs, 2008)
The main diagnostic and therapeutic procedures in sepsis were determined by the Surviving Sepsis Campaign in 2004. Meningococcal disease is a very dangerous disease, because of the virulence of Neisseria meningitidis. Early recognition and treatment of meningococcal infection significantly decrease mortality due to full-symptom disease.